An introduction to derivatives and risk management / Don M. Chance, Robert Edwin Brooks - Chance, Don M.
Give your students a solid understanding of financial derivatives and their use in managing the risks of financial decisions with this leading text. Chance/Brooks' "An introduction to derivatives and risk management", offers an outstanding blend of institutional material, theory, and practical applications. The latest financial information throughout this edition and timely Internet updates on the text's website ensure the material reflects the most recent changes in today's financial world. You'll find detailed, but flexible, coverage of options, futures, forwards, swaps, and risk management as well as a balanced introduction to pricing, trading, and strategy. You can easily address only the topics and chapters that best fit your needs. A variety of practical end-of-chapter applications, memorable examples from real businesses throughout the learning features, and minimal use of technical mathematics keep the text's presentation accessible and engaging. Stock-Trak software, available with each new text, provides additional value and opportunity for practical working experience. Count on this exceptional text to provide the thorough introduction to derivatives and risk management that students need for success in financial business today